PERAN PENGAWAS SEKOLAH DALAM PENDAMPINGAN PEMBELAJARAN DI SEKOLAH BINAAN SMP - Naomi Kogoya; Yulius Mataputun; Juliana Waromi; C. Tanta; Robert Masreng; Monika Gultom (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The shift in the supervisory function of supervisors to become partners in the Freedom to Learn pillar to improve the quality of national education is the background to this research. This issue demands a reconstruction of supervisory governance in underdeveloped, frontier, and outermost (3T) regions that are vulnerable to managerial stagnation. The focus of this research is to analyze the role of school supervisors in supporting learning at SMP Negeri 4 Wamena, Jayawijaya Regency, Papua Mountains Province. A qualitative approach with an exploratory case study design was applied, where data were collected through participant observation, in-depth interviews with six selected informants, and a documentary study of the school profile that mentors 161 students. Data analysis techniques were carried out interactively through stages of condensation, data presentation, and drawing conclusions. The research findings reveal that the supervisory role has not been optimal and remains trapped in administrative-conventional patterns, as evidenced by the absence of an official work program since 2018 and minimal clinical supervision. The main conclusion confirms that the effectiveness of mentoring is systemically hampered by extreme geographic constraints, excessive workloads, and lack of access to electricity. This research recommends the implementation of the Reflection-Contextual Mentoring Model through an intensive block visit strategy and the use of local natural media to realize the equal distribution of sustainable education quality standards in the interior of Papua. ABSTRAK Pergeseran fungsi inspektif pengawas menjadi mitra pendamping dalam pilar Merdeka Belajar guna meningkatkan mutu pendidikan nasional melatarbelakangi penelitian ini. Masalah tersebut menuntut adanya rekonstruksi tata kelola kepengawasan di wilayah tertinggal, terdepan, dan terluar (3T) yang rentan mengalami stagnasi manajerial. Fokus penelitian ini adalah menganalisis peran pengawas sekolah dalam pendampingan pembelajaran di SMP Negeri 4 Wamena, Kabupaten Jayawijaya, Provinsi Papua Pegunungan. Pendekatan kualitatif dengan rancangan studi kasus eksploratif diterapkan, di mana data dikumpulkan melalui observasi partisipatif, wawancara mendalam terhadap enam informan terpilih, dan studi dokumentasi terhadap profil sekolah yang membina 161 siswa. Teknik analisis data dijalankan secara interaktif melalui tahapan kondensasi, penyajian data, serta penarikan kesimpulan. Temuan penelitian mengungkapkan bahwa peran pengawas belum berjalan optimal dan masih terjebak pada pola administratif-konvensional, yang dibuktikan dengan ketiadaan program kerja resmi sejak 2018 serta minimnya supervisi klinis. Simpulan utama menegaskan bahwa efektivitas pendampingan terhambat secara sistemik oleh kendala geografis ekstrem, beban kerja berlebih, dan ketiadaan akses listrik. Riset ini merekomendasikan penerapan Model Pendampingan Refleksi-Kontekstual melalui strategi kunjungan blok intensif dan pemanfaatan media alam lokal demi mewujudkan pemerataan standar mutu pendidikan yang berkelanjutan di pedalaman Papua.